The Impact Of The Potential Development Of Tourism Villages On The Economy In Indonesia - Ayu Esteka Sari (Citakonsultindo, 2025)
This study aims to analyze the influence of the determinants of tourism village development on the increase of the economy in Indonesia. The main focus of the research is on the determinants of tourist villages. The method used includes quantitative data analysis from various tourism villages in Indonesia to understand the relationship between the development of tourism villages and the improvement of the economy in Indonesia, converted on Gross Regional Domestic Product (GRDP). The results of the study show that tourism villages do not have a significant effect on the Gross Regional Domestic Product (GRDP) at the district level in Indonesia, with a constant value of 9.535. Result of the value P>|t| of 0.567 with a t calculation of 0.57, which can be interpreted as tourism villages do not have a significant effect on the Gross Regional Domestic Product (GRDP) at the district level in Indonesia.